CASE SERIES OF BURKHOLDERIA PSEUDOMALLEI CAUSING MELIOIDOSIS (PULMONARY, CEREBRAL, AND SPLENIC ABSCESS) - S, Prasanna; Mahajan, Mayuri; Mahajan, Nikhil (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Burkholderia pseudomallei is soil saprophytic Gram-negative bacilli that cause a fatal disease called melioidosis. Melioidosis is capable of causing cutaneous infection and systemic infections in the respiratory tract, cardiovascular, gastrointestinal, urinary, skin and soft tissue, and musculoskeletal and central nervous systems. Here, we report rare forms of pulmonary, cerebral, and splenic abscess case series of melioidosis caused by B. pseudomallei. Imported cases have been reported among tourists, immigrants, and soldiers who returned from endemic areas. The acquisition of infection is through percutaneous, inhalation, and ingestion of contaminated water; person-to-person transmission is very rare. Melioidosis cases are primarily found in the rainfall season and are usually associated with risk factors such as diabetes, alcoholism, and chronic renal diseases. However, 20–26% of cases were not associated with predisposing conditions. The identification is based on colony morphology, Gram stain, antibiotic susceptibility testing, and other supportive automated and molecular assays when we suspect B. pseudomallei. There are two phases, the intensive and eradication phases, in managing melioidosis. In the intensive phase, ceftazidime for 2 weeks showed efficacy in almost 50% of cases, and the eradication phase treatment with co-trimoxazole and doxycycline or amoxicillin/clavulanic acid for 3–6 months showed an excellent response. The improper clinical diagnosis and management of B. pseudomallei can lead to complications. Hence, early diagnosis with microbiological approaches such as culture, biochemical reactions, or automated systems available and antimicrobial sensitivity testing will cure the patient quickly without mortality.